Faktor Hidayah dalam Dakwah - Kamaluddin Ritonga (Hikmah, 2018)
Da'wah as one means of broadcasting Islam became the obligation of Muslims who did not escape from the various challenges and failures, both da'wah was addressed to non Muslim md'u, as well as to the already Muslim. Public response to da'wah, among others, consists of groups that receive immediately, some are pretending to receive and there are groups who reject and even oppose and obstruct da'wah. In terms of religious com- pliance there is a mad'u who is supposedly converted to Islam but can not, on the contrary there are people who unexpectedly turn out to be converts into Islam. Therefore, what is the guidance and how can da'i be done in achieving the success of da'wah? Hidayah consists of emapat kinds, that is first hidayah instinct, senses of mind and fitrah. Both guidance dalalah wal irsyad, namely the direction of religious science in the form of invitation, guidance and education. Hidayah this is the duty of the Prophet and da'i. The three guidance of taufik or ma'unah, ie, faith and Islam are inspired to the human heart. The four hidayah heaven received later in the day. Prophet and da'i can only give guidance in the form of wal-irshad in the form of invite, guide and teach people about aqidah, pikih, law and morals, while taufik hidayah ma'unah in the form of faith and piety, only God can give it because He is who knows who is heretical and who is entitled to guidance. The prophet and da'i are not entitled to give the guidance of this ma'unah to man, even to his own loved ones who loved and loved. To obtain the ma'unah guidance, preachers let guiding mad'unya so tauhid, pious charity, sole trust, pray and stay away from polytheism and hypocrisy.Keyword: Hidayah, Da'wah.